Ignorance and Vulnerability in Post-Colonial Diplomacy - Christopher Prior; Falko Schnicke (Österreichische Zeitschrift für Geschichtswissenschaften)
In the post-colonial era, both former colonizing and former colonized powers found themselves engaged in a dramatic renegotiation of diplomatic relationships. Against this backdrop, the access to, or withholding of, information and understanding about other states became a key asset in any mobilization of leverage and maintenance of agency. This article draws upon the case studies of the UK’s diplomatic relationships with African states and India in order to emphasize the virtue of combining New Diplomatic History (NDH) and history-of-knowledge approaches. Competing knowledges, and the denying of access to knowledge to others, could be mobilized in pursuit of competing agendas, both across and within national governments. The fragilities and contingencies behind the availability of information, coupled with enduring colonial-era prejudices which others could exploit, created areas of ignorance, and rendered governmental knowledge processes vulnerable.